Pengaruh Motivasi Akademik terhadap Prestasi Matematika Siswa Di SDN 1 Mata Ie Aceh Besar - Darma Darma; Linda Vitoria; Mislinawati Mislinawati (Pesona Dasar : Jurnal Pendidikan Dasar dan Humaniora, 2022)
In learning mathematics, it appears that students are less enthusiastic in participating in learning and their scores are low. This study aims to determine whether there is a significant influence of academic motivation on mathematics achievement at SDN 1 Mata Ie Aceh Besar. This research is a study that looks at the level of students' academic motivation through a scale of elementary students' mathematics learning motivation. The population in this study were all students in grades IV, V, and VI at SDN 1 Mata Ie Aceh Besar totaling 81 students and the samples were taken using a stratified random sampling technique where from each class 10 students were taken randomly, namely 5 students whose scores reached KKM and 5 students whose scores have not reached the KKM so that the total sample in this study amounted to 30 students. Data collection is done in two ways, namely by looking at the scores of students' academic motivation and the value of student report cards, especially in learning mathematics. To see the significant effect of academic motivation on students' mathematical achievement, the product moment correlation test and the F test at a significant level of 0.05 were used. From the results of data analysis, the value of Fcount = 3.029 and Ftable = 2.052, namely Fcount Ftable. Thus HO is rejected, so Ha is accepted and it can be concluded that there is a significant influence of academic motivation on mathematics achievement at SDN 1 Mata Ie Aceh Besar.